(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article discusses the involvement of children with hearing and developmental disabilities in art, the development of their artistic abilities and the formation of their speech. One of the main tasks of the visual arts methodology is the development of cognitive activity of children with developmental disabilities. The teacher teaches children to perceive the world around them, objects, and understand their essence. Children with hearing impairments, on the contrary, acquire knowledge through visual analyzers. This article covers the process of perception, imagination, visual activity and sensory education of children with hearing impairments.